2007
DOI: 10.1007/s00247-007-0503-4
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal synostosis in X-linked hypophosphatemic rickets and related diseases

Abstract: There is an increased risk of sagittal synostosis in hypophosphatemic rickets and related diseases in children. The appearance of the cranial vault in this type of synostosis can vary from that seen in nonsyndromic synostosis. In this setting, careful clinical and imaging follow-up is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 14 publications
1
43
1
Order By: Relevance
“…3,21,27 The sagittal suture is the most commonly affected in 6 of 10 in our series, which correlates with the compiled data in the literature (23/28 cases). Greater age at initial presentation for hypophosphatemic rickets and milder symptomatology are correlated with a lower incidence and severity of craniosynostosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3,21,27 The sagittal suture is the most commonly affected in 6 of 10 in our series, which correlates with the compiled data in the literature (23/28 cases). Greater age at initial presentation for hypophosphatemic rickets and milder symptomatology are correlated with a lower incidence and severity of craniosynostosis.…”
Section: Discussionsupporting
confidence: 90%
“…Prolonged treatment with aluminum-magnesium hydroxides in particular can limit renal tubular resorption and gastrointestinal absorption of phosphorus, leading to severe depletion. 3 In addition, soy-based formulas, which contain phytates, may impair absorption of minerals, including calcium, phosphate, iron, and zinc, 5 which exacerbates the problem because their use is often coincident with antacids in infants with colic. At this time, it is recommended to use aluminum-containing antacid therapy cautiously and in low doses with routine monitoring of serum calcium and phosphorous if prolonged therapy is indicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are classical pathways that are involved in early embryonic development. But also, many of the gene defects may act through causing perturbations in osteogenesis, such as filaminopathies, hypophosphatasia [Currarino, 2007;Murthy, 2009], mucopolysaccharidoses [Ziyadeh et al, 2013], osteosclerosis [Kato et al, 2002;Kwee et al, 2005;Simpson et al, 2007Simpson et al, , 2009, and pycnodysostosis [Osimani et al, 2010;Bertola et al, 2011;Berenguer et al, 2012;Caracas et al, 2012;Twigg and Wilkie, 2015]. These diagnoses include potentially treatable conditions, for which early recognition is particularly important [Wilkie et al, 2017], and more and more mutations are being identified in genes that are involved in brain development or that are associated with intellectual disability and/or behavioral anomalies (such as ASXL1 , ANKDR11 , KAT6A , KMT2D , and ZEB2 ) [Twigg and Wilkie, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…3 Rickets may be associated with a variety of cranial bone disorders -craniosynostosis and the presence of cerebellar tonsillar descent being the most notablethat can result in an increase in intracranial pressure. [4][5][6][7][8][9][10] In our patient there was a suspicion of intracranial hypertension associated with XLH. Unfortunately, a lumbar puncture with measurement of the opening pressure could not be performed, as this procedure is considered to be dangerous in patients with an existing cerebellar tonsillar descent.…”
Section: Discussionmentioning
confidence: 99%